"Ser alguém na vida": uma análise sócio-antropológica da gravidez/maternidade na adolescência, em Belém do Pará, Brasil - PANTOJA, Ana Lídia Nauar (2015)
Focused on a group of low-income youth in Belém, Pará State, Brazil, this study discusses the issue of adolescent pregnancy and motherhood from a socio-anthropological perspective. Aimed at an understanding of the cultural meanings of this event in this context, the study suggests that for adolescent girls, it does not mean a break with life projects. On the contrary, pregnancy and motherhood are valued to the extent that they produce changes in social status for the girls, in terms of affirmation of projects for social mobility in the future, thus justifying the continuity of studies in the face of difficulties imposed by the situation.